Severe Erosive Pill Esophagitis Induced by Crizotinib Therapy: A Case Report and Literature Review - Patrick Jung; Kyle J. Fortinsky; Zane R. Gallinger; Piero Tartaro (Case Reports in Gastrointestinal Medicine)
Previous case reports have described esophagitis thought to be secondary to crizotinib, an oral tyrosine-kinase inhibitor used in the treatment of anaplastic lymphoma kinase- (ALK-) positive non-small cell lung cancer (NSCLC). In those reports, the interval development of esophagitis was between two days and three months after initiating or reinitiating crizotinib therapy. We present a woman who developed ulcerative esophagitis ten months after beginning crizotinib therapy, which is highly unusual. We believe the provoking factor was a change in her medication administration routine, done to accommodate religious practices during the period of Ramadan. This case illustrates the mechanism of pill esophagitis and reinforces the importance of patient education when it comes to medication administration. Clinicians may consider early imaging or investigations in patients with concerning symptomatology in the context of crizotinib therapy or other offending medications. Future research may help to uncover additional risk factors for this exceedingly rare diagnosis in this patient population. Most importantly, this case highlights nonpharmacologic ways to improve tolerability and decrease adverse effects of a highly effective chemotherapeutic agent.